Prevention and treatment of relapse after stem cell transplantation in lymphoid malignancies - Sureda, Anna; Dreger, Peter (Bone marrow transplantation, 2019)
Relapse is now the major cause of treatment failure after allogeneic HSCT (alloHSCT). Many novel strategies to address this critical issue are now being developed and tested. At the 3rd International Workshop on Biology, Prevention, and Treatment of Relapse held in Hamburg, Germany in November 2016, international experts presented and discussed recent developments in the field. Some approaches may be applicable to a wide range of patients after transplant, whereas some may be very disease-specific. We present a report from the session dedicated to issues related to prevention and treatment of relapse of lymphoid malignancies after alloHSCT. This session included detailed reviews as well as forward-looking commentaries that focused on Hodgkin lymphoma, chronic lymphocytic leukemia and mantle cell lymphoma, diffuse large cell and follicular lymphoma, and multiple myeloma.
Published: 24 May 2018
Gesehen am 29.04.2019